Dysmetabolic Iron Overload Syndrome and Non-alcoholic Fatty Liver Disease - Grigorescu, Ioana (Medicine and Pharmacy Reports, 2014)
The involvement of high values of iron in different diseases, such as nonalcoholic fatty liver disease (NAFLD), insulin resistance, diabetes mellitus, metabolic syndrome and cardiovascular diseases, created the so called dysmetabolic iron overload syndrome (DIOS). The molecular mechanism is not known exactly, but a possible pathogenesis might imply distrubances in oxidative stress and injury of the DNA-structure, in the cellular transport of iron (hepcidin), and in the defective release of adipokines. The target organs in DIOS and the induced disorders are: pancreas (insulin resistance, diabetes mellitus), liver (severe steatosis, progressive fibrosis and malignant transformation), heart (acute myocardial infarction) and arteries (atherogenesis). The typical histological location in hepatic iron overload is the sinusoidal space. Therapeutical response to dietary restriction and phlebotomy include decrease of hepatic and metabolic tests, lower risks of progressive fibrosis in liver and hepatocarcinoma and cardiovascular mortality.